TECHNOLOGICAL CAPACITIES OF COUNTRIES AT THE BEGINNING OF THE 21ST CENTURY - Kuźnar, Andżelika (Ekonomia i Prawo. Economics and Law, 2013)
Nowadays the wealth of nations depends to the largest extent on their technological capabilities. The paper analyses how the role of certain groups of countries changes with respect to these capabilities. Empirical study shows that the further domination of the Triad countries in the development of the technological capability is not certain. Their position is threaten by the growing competition from fast-growing countries in Asia. These countries play an increasingly important role in R&D spending, they also import new technologies, as seen in the increasing expenditures on license fees. They benefit from rapidly growing number of graduates, especially in technical fields, which are the key to building the innovative capacity of firms. The share of Asian inventors receiving patent protection in the United States, European Union and Japan also steadily increases. These trends have even been deepened during the last economic crisis, which has affected developed countries more severely than most developing countries.